Đạo hàm của hàm số (y = (( (3(x^2) - 2x + 1) )^(dfrac(1)(4)))) là:

Lưu lại

Đạo hàm của hàm số $y = {\left( {3{x^2} - 2x + 1} \right)^{\dfrac{1}{4}}}$ là:

Đáp án: B

Ta có:

$y' = \dfrac{1}{4}{\left( {3{x^2} - 2x + 1} \right)^{ - \dfrac{3}{4}}}.{\left( {3{x^2} - 2x + 1} \right)^\prime }$$ = \dfrac{1}{4}{\left( {3{x^2} - 2x + 1} \right)^{ - \dfrac{3}{4}}}.\left( {6x - 2} \right)$ $ = \dfrac{{\left( {3x - 1} \right){{\left( {3{x^2} - 2x + 1} \right)}^{ - {\textstyle{3 \over 4}}}}}}{2}$

Chọn B.

TOP THÀNH VIÊN NỔI BẬT

    Xem top 100 thành viên